Thermosetting low-dielectric insulation sheet
Patent Information
- Application Number
- JP2023132476
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0019】 本発明のFCCL用、又はIC基板用熱硬化型低誘電絶縁シートは、誘電率、誘電正接に優れる。
Smart Images

Figure 2025027592000001 
Figure 2025027592000002 
Figure 2025027592000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermosetting low dielectric insulating sheet. [Background technology]
[0002] Patent Document 1 discloses an insulating resin sheet having a heat-resistant film and a thermosetting resin composition layer formed on both sides of the heat-resistant film, in which the etching amount per unit area of the heat-resistant film (E1) and the etching amount per unit area of the cured product of the thermosetting resin composition layer (E2) satisfy E1 / E2=0.5 to 3, and a multilayer printed wiring board in which an insulating layer is formed by this insulating resin sheet. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2014-187091 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a new thermosetting low dielectric insulating sheet for FCCL or IC substrate. [Means for solving the problem]
[0005] By controlling the water absorption rate of the thermosetting low dielectric insulating sheet within a certain range, the inventors have been able to produce a thermosetting low dielectric insulating sheet that has excellent dielectric constant and dielectric tangent and is suitable for FCCL or IC substrates.
[0006] The present invention encompasses the following laminate (thermosetting low dielectric insulating sheet) for FCCL or IC substrate.
[0007] Section 1. A laminate comprising: The laminate has a three-layer structure including at least a heat-resistant film and a thermosetting resin composition layer on each side of the heat-resistant film, The laminate has a water absorption rate of 0.5% by mass or less, Laminate (thermosetting low dielectric insulating sheet) for FCCL or IC substrate.
[0008] Section 2. The laminate has a Dk dielectric constant of 2.8 or less at 10 GHz; and 2. The laminate according to item 1, wherein the laminate has a Df dielectric tangent at 10 GHz of 0.025 or less.
[0009] Section 3. The heat-resistant film is a polyimide film, 2. The laminate according to item 1, wherein the thermosetting resin composition layer is a resin composition layer made of a polyether resin.
[0010] Section 4. Item 2. The laminate according to item 1, wherein the thermosetting resin composition layer contains silica.
[0011] Section 5. Item 2. The laminate according to item 1, wherein the thermosetting resin composition layer contains at least one flame retardant selected from the group consisting of a phosphinate compound, a phosphine oxide compound, a polyphosphate compound, and a phosphonium salt compound.
[0012] Section 6. Item 2. The laminate according to item 1, further comprising a copper foil on one or both sides of the laminate.
[0013] Section 7. 7. The laminate according to item 6, wherein the copper foil has a roughness Rz of 2 μm or less.
[0014] Section 8. The heat-resistant film has a thickness of 1 μm to 50 μm, The thermosetting resin composition layers each have a thickness of 5 μm to 100 μm, The copper foil has a thickness of 1 μm to 38 μm for each layer, 7. The laminate according to item 6, wherein the laminate has a total thickness of 12 μm to 326 μm.
[0015] Section 9. 9. An FCCL or an IC substrate comprising the laminate according to any one of items 1 to 8.
[0016] The laminate (thermosetting low dielectric insulating sheet) of the present invention is preferably used for a build-up layer of a multilayer printed wiring board.
[0017] The present invention includes a multilayer printed wiring board having an insulating layer formed from the laminate of the present invention.
[0018] The laminate of the present invention is excellent in dielectric constant and dielectric loss tangent when used for FCCL or IC substrate. Effect of the Invention
[0019] The thermosetting low dielectric insulating sheet for FCCL or IC substrate of the present invention is excellent in dielectric constant and dielectric loss tangent. [Brief description of the drawings]
[0020] [Figure 1] 1 is a diagram showing a thermosetting low dielectric insulating sheet of the present invention. [Diagram 2] 1 is a diagram showing a thermosetting low dielectric insulating sheet of the present invention. [Diagram 3] FIG. 1 is a diagram showing a thermosetting low dielectric insulating sheet of Example 1. [Figure 4] FIG. 13 is a diagram showing a thermosetting low dielectric insulating sheet of Comparative Example 2. [Diagram 5] FIG. 13 is a diagram showing a thermosetting low dielectric insulating sheet of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present invention will be described in detail below.
[0022] The embodiments of the present invention are intended to provide a better understanding of the gist of the invention, and unless otherwise specified, do not limit the content of the invention.
[0023] In this specification, the terms "comprise" and "containing" are concepts which encompass all of "comprise," "consist essentially of," and "consist of."
[0024] In this specification, when a numerical range is indicated as "A to B," it means "not less than A and not more than B."
[0025] In this specification, the designations parts, % etc. are generally used.
[0026] In this specification, the terms "parts by mass," "parts by weight," "% by mass," and "% by weight (wt%)" are generally used.
[0027] The present invention encompasses the following laminate for an FCCL or an IC substrate.
[0028] [1] Laminate (thermosetting low dielectric insulating sheet) The thermosetting low dielectric insulating sheet (laminate) of the present invention will be described with reference to FIG.
[0029] The thermosetting low dielectric insulating sheet of the present invention is characterized by its water absorption adjusted to a specific range for use in FCCL or IC substrates. The thermosetting low dielectric insulating sheet for FCCL or IC substrates of the present invention has excellent dielectric constant and dielectric loss tangent due to the water absorption adjusted to 0.5 mass % or less.
[0030] FCCL: Flexible Copper Clad Laminate, a copper-clad laminate for flex circuits, a material for FPCs (Flexible Printed Circuits) made by laminating thin copper foil and insulating film.
[0031] IC: Integrated Circuit.
[0032] In order to be compatible with the millimeter wave range, it is necessary to reduce the dielectric loss of insulating materials. Dielectric loss occurs when energy is lost as heat when an AC electric field is applied to a dielectric, which causes signal degradation. In particular, in the millimeter wave range, the effect of signal degradation due to dielectric loss is large, so the selection of insulating materials for printed circuit boards is important.
[0033] As signals become faster and more frequent, there is a demand for thermosetting compositions that can maintain a sufficiently low dielectric constant under these conditions and form a cured product that exhibits a sufficiently low dielectric loss tangent. In particular, in advanced material applications, there is a demand for improved heat resistance and dielectric properties of materials and compositions. As a material that combines heat resistance with a low dielectric constant and low dielectric loss tangent, maleimide resin is preferably used. In particular, maleimide resins used in printed circuit board materials are required to have improved performance in terms of fine pattern processability, dimensional stability, heat resistance, and high-frequency electrical properties. As a printed circuit board material that does not impair heat resistance and exhibits a low dielectric constant, for example, a polymaleimide resin obtained by reacting an oligomer obtained by reacting an aralkyl alcohol compound and an aniline compound with maleic anhydride is used.
[0034] With the start of 5G communication, communication speeds are increasing and communication volumes are becoming larger, and communication in the high frequency range has begun. Communication devices such as mobile terminals require low signal transmission loss in the wiring of the circuit board and high signal propagation speed. In particular, in communication in the high frequency range of several tens of GHz or more, the higher the frequency, the greater the signal transmission loss, so the insulating material of the circuit board is required to have a low dielectric constant and a low dielectric loss tangent.
[0035] From the viewpoint of shortening the wiring distance as much as possible and accelerating the signal propagation speed, it is preferable to collectively stack an antenna substrate for receiving a signal and a substrate on which semiconductors and electronic components for processing the signal are mounted, and to integrate them into a package. At this time, the insulating material of the antenna substrate is required to have a low dielectric constant and a low dielectric loss tangent, and is required to be able to conform to and adhere to the substrate when heated and pressurized for collectively stacking. From these viewpoints, it is preferable to use a thermosetting resin composition for the circuit substrate, for example, a resin composition mainly composed of an epoxy resin, a polyphenylene ether resin, or the like.
[0036] Information transmission devices such as network equipment require high-speed signals. To achieve high-speed signals, it is necessary to improve the signal propagation speed and achieve low transmission loss in the high-frequency range for the high-frequency circuit boards used in the information transmission devices. Information transmission devices such as network equipment preferably use high-frequency circuit boards with low dielectric constant and low dielectric loss.
[0037] In order to improve the characteristics of low dielectric constant and low dielectric loss, it is important to improve the dielectric properties of the insulating layer that constitutes the high frequency circuit board. The resin material that constitutes the insulating layer of the high frequency circuit board is preferably an epoxy resin, a polyimide resin, or the like. For example, a thermoplastic liquid crystal polymer, which is a copolymer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, is molded as the resin material, and then heat-treated to control the dielectric constant and dielectric loss.
[0038] As a manufacturing method for FCCL for electronic circuit boards or laminates for IC boards, epoxy resin is impregnated into glass cloth, dried, and copper foil is laminated on both sides, or resin is applied to copper foil and dried to create RCC (Resin Coated Copper). FCCL is manufactured by laminating RCC on both sides of various flexible substrates (polyimide, LCP (Liquid Crystal Polymer)).
[0039] Polyimide (PI) generally has high dielectric constant and dielectric dissipation factor as physical properties, and in conventional FPCs, it has issues such as high delay and loss of signals with high frequency components, and it easily absorbs moisture from the air (high water absorption rate). Because water is a substance with an extremely high dielectric constant and dielectric dissipation factor, if the water absorption rate of the board increases, the degree of signal delay and loss will inevitably increase as well. For this reason, low water absorption properties are required for the constituent materials of FPCs for high-speed transmission.
[0040] The thermosetting low dielectric insulating sheet for FCCL or IC substrate of the present invention exhibits a low dielectric constant and a low dielectric tangent due to the combination of a polyimide with a resin having low water absorption, a low dielectric constant, and a low dielectric tangent.
[0041] Conventionally, fluoro-PTFE and LCP-based materials have been considered for use as substrates for high-speed transmission (millimeter wave, 28 GHz and above). When fluoro-PTFE is used for the substrate, copper foil is thermally laminated (fused) to both sides to maintain adhesion strength, but issues arise with the surface roughness of the copper foil. If the copper foil surface is rough, adhesion strength increases, but if it is smooth, adhesion strength decreases. When fluoro-PTFE is used for the substrate, issues arise with processability (laser drilling) and dimensional stability.
[0042] When using LCP for the substrate, LCP is difficult to obtain. Orientation processing after LCP film formation is complicated and expensive. When using LCP for the substrate, copper foil is thermally laminated on both sides of the LCP, which creates the same problems as the fluorine-based PTFE.
[0043] PI is generally considered to have a high water absorption rate and is unsuitable for high-speed transmission. MPI (Modified-PI, modified polyimide) has improved the above issues and can be used in Sub6. However, MPI still has the above issues in the 5G (28GHz) band.
[0044] The thermosetting low dielectric insulating sheet of the present invention is a film for high-speed transmission compatible with 6G using a PI film for FCCL or IC substrate.
[0045] The present invention relates to a resin having a low water absorption rate (0.2 mass%) (for example, "JSR ELPAC TM Based on our "HC-G series," we used a resin with good adhesion to smooth copper foil with low water absorption, and after careful consideration of the thickness configuration of the resin and PI film (thermosetting low dielectric insulating sheet), we developed a film that can be used for 5G.
[0046] The thermosetting low dielectric insulating sheet of the present invention is a laminate having a three-layer structure of resin / heat-resistant film (preferably PI film) / resin, and is characterized in that the laminate has a water absorption rate of 0.5 mass % or less. The thermosetting low dielectric insulating sheet of the present invention is a thermosetting low dielectric insulating sheet excellent in dielectric constant and dielectric loss tangent for FCCL or IC substrate, by making the laminate have a water absorption rate of 0.5 mass % or less.
[0047] Using the thermosetting low dielectric insulating sheet of the present invention, a low water absorption varnish (paint) was examined by changing the moisture thickness of the substrate. As a result, it was found that by coating a thin (10 μm) low absorption PI on both sides with a low water absorption varnish, a high frequency substrate with low Dk and low Df characteristics can be created for use as an FCCL or IC substrate.
[0048] 1 shows a three-layer structure having a thermosetting resin composition layer on both sides of a heat-resistant film of this embodiment. The three-layer structure having a thermosetting resin composition layer on both sides of a heat-resistant film of this embodiment includes a heat-resistant film 101 having an upper surface and a back surface, a first thermosetting resin composition layer 102a and a second thermosetting resin composition layer 102b on the upper surface and back surface of the heat-resistant film 101, respectively, and a copper foil 103a on the upper surface of the first thermosetting resin composition layer 102a and a copper foil 103b on the back surface of the second thermosetting resin composition layer 102b.
[0049] Heat-resistant film 101 is preferably a polyimide (PI) film made of an insulating material. Heat-resistant film 101 preferably has a thickness of 1 μm to 50 μm.
[0050] The raw materials of the first thermosetting resin composition layer 102a and the second thermosetting resin composition layer 102b on the upper and lower surfaces of the heat-resistant film 101 are preferably polyether-based resin and styrene-based resin. The thicknesses of the first thermosetting resin composition layer 102a and the second thermosetting resin composition layer 102b are each preferably 5 μm to 100 μm, for example.
[0051] Copper foil 103a and copper foil 103b are provided on the upper surface of first thermosetting resin composition layer 102a and the rear surface of second thermosetting resin composition layer 102b, respectively. The thickness of copper foil 103a and copper foil 103b is preferably 1 μm to 38 μm.
[0052] (1) Heat-resistant film The laminate (thermosetting low dielectric insulating sheet) of the present invention has a three-layer structure having at least a heat-resistant film and a thermosetting resin composition layer on each side of the heat-resistant film.
[0053] The glass transition temperature of the heat-resistant film is preferably 150° C. or higher, more preferably 170° C. or higher, further preferably 200° C. or higher, and particularly preferably 250° C. or higher. The upper limit of the glass transition temperature of the heat-resistant film is generally 500° C. or lower. The "glass transition temperature" is measured according to the method described in JIS K 7179. Specifically, it is measured using thermomechanical analysis (TMA), dynamic mechanical analysis (DMA), or the like.
[0054] The linear thermal expansion coefficient of the heat-resistant film is preferably 30 ppm / ° C. or less, more preferably 20 ppm / ° C. or less, even more preferably 15 ppm / ° C. or less, and particularly preferably 10 ppm / ° C. or less. From a practical viewpoint, the lower limit of the linear thermal expansion coefficient of the heat-resistant film is preferably −20 ppm / ° C. or more, more preferably −15 ppm / ° C. or more, and even more preferably −10 ppm / ° C. or more.
[0055] Examples of the heat-resistant film include heat-resistant resin films such as polyimide (PI), liquid crystal polymer, polyphenylene sulfide, polyethylene naphthalate, polyether ether ketone, polybenzimidazole, aramid, polyamideimide, and polyetherimide.
[0056] The resin constituting the heat-resistant film may be one of these resins, or a mixture (blend) of two or more of them.
[0057] The heat-resistant film is preferably a polyimide (PI) film.
[0058] The heat-resistant film may be subjected to a surface treatment such as a corona treatment or a plasma treatment.
[0059] (2) Thermosetting resin composition layer The laminate of the present invention has a three-layer structure having at least a heat-resistant film and a thermosetting resin composition layer on each side of the heat-resistant film.
[0060] thermosetting resin The thermosetting resin composition layer is preferably a resin composition layer made of a polyether-based resin.
[0061] The polyether resin is preferably an aromatic polyether polymer, which is a polymer mainly composed of aromatic rings and contains at least an ether bond in the repeating unit as a linking mode of aromatic ring units.
[0062] The structure of the aromatic polyether polymer is preferably aromatic polyether, aromatic polyether ketone, aromatic polyether ether ketone, aromatic polyether ketone ketone, aromatic polyether ether ketone ketone, aromatic polyether ketone ether ketone ketone, aromatic polyether imide, aromatic polyether sulfone, etc.
[0063] From the viewpoints of chemical stability and cost, it is preferable to use an aromatic polyether ketone polymer, a polyether sulfone polymer, or the like as the aromatic polyether polymer. Furthermore, from the viewpoints of mechanical strength, dimensional stability, and physical durability, an aromatic polyether ketone polymer is used.
[0064] An aromatic polyether ketone polymer is a polymer mainly composed of aromatic rings, and contains at least an ether bond and a ketone bond in the repeating unit as a mode of linking aromatic ring units.
[0065] An aromatic polyethersulfone polymer is a polymer mainly composed of aromatic rings, in which the aromatic ring units are linked together via at least ether bonds and sulfone bonds.
[0066] The polyether-based resin is preferably a polyetherimide resin, a polyethersulfone resin, a polyetheretherketone resin, etc. The polyether-based resin is preferably a heat-resistant, low-dielectric insulating material based on aromatic polyether.
[0067] inorganic filler The thermosetting resin composition layer preferably contains an inorganic filler, which is preferably silica, alumina, mica, silicate, barium sulfate, magnesium hydroxide, titanium oxide, etc., more preferably silica, alumina, etc., and particularly preferably silica, such as amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, and spherical silica.
[0068] The inorganic filler may be used alone or in combination of two or more kinds (blend).
[0069] From the viewpoint of improving the filling property into the thermosetting resin composition, it is preferable to use spherical fused silica. The thermosetting resin composition layer preferably contains silica.
[0070] Flame retardants The thermosetting resin composition may contain a flame retardant to improve flame retardancy. The flame retardant is preferably an organic phosphorus-based flame retardant, an organic nitrogen-containing phosphorus compound, a nitrogen compound, a silicone-based flame retardant, a metal hydroxide, or the like.
[0071] The organic phosphorus-based flame retardant is preferably a phenanthrene-type phosphorus compound, a phosphorus-containing benzoxazine compound, or a phosphoric acid ester compound.
[0072] The organic nitrogen-containing phosphorus compound is preferably a phosphoric acid ester amide compound, a phosphazene compound, etc. The metal hydroxide is preferably magnesium hydroxide, aluminum hydroxide, etc.
[0073] The thermosetting resin composition layer preferably contains at least one flame retardant selected from the group consisting of a phosphinate compound, a phosphine oxide compound, a polyphosphate compound, and a phosphonium salt compound.
[0074] The phosphinate compound preferably used includes aluminum dialkylphosphinate, aluminum trisdiethylphosphinate, aluminum trismethylethylphosphinate, aluminum trisdiphenylphosphinate, zinc bisdiethylphosphinate, zinc bismethylethylphosphinate, zinc bisdiphenylphosphinate, titanyl bisdiethylphosphinate, titanyl bismethylethylphosphinate, and titanyl bisdiphenylphosphinate.
[0075] As the phosphine oxide compound, preferably, xylylene bisdiphenylphosphine oxide, phenylene bisdiphenylphosphine oxide, biphenylene bisdiphenylphosphine oxide, naphthylene bisdiphenylphosphine oxide, or the like is used.
[0076] As the polyphosphate compound, melamine polyphosphate, melam polyphosphate, melem polyphosphate, etc. are preferably used.
[0077] As the phosphonium salt compound, preferably, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium bromide, or the like is used.
[0078] The flame retardants may be used alone or in combination (blend) of two or more kinds.
[0079] Preparation of Thermosetting Resin Composition The thermosetting resin composition is produced as a resin varnish by appropriately mixing the components and, if necessary, kneading or mixing the mixture using kneading means such as a triple roll mill, ball mill, bead mill, or sand mill, or stirring means such as a super mixer or planetary mixer.
[0080] When the laminate of the present invention is used for forming an interlayer insulating layer of a multilayer printed wiring board, etc., one of the thermosetting resin composition layers formed on both sides of the heat-resistant film becomes a thermosetting resin composition layer for forming a conductor layer, and the other becomes a thermosetting resin composition layer for laminating an inner layer circuit board.
[0081] The organic solvent used in preparing the resin varnish of the thermosetting resin composition is preferably a ketone such as acetone, methyl ethyl ketone, cyclohexanone, etc.; acetate esters such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, carbitol acetate, etc.; cellosolves such as cellosolve and butyl cellosolve, carbitols such as carbitol and butyl carbitol, aromatic hydrocarbons such as toluene and xylene, amides such as dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc.
[0082] The organic solvent may be used alone or in combination of two or more kinds (blend).
[0083] (3)Copper foil In the laminate of the present invention, from the viewpoints of preventing adhesion of dust and the like, ease of handling when used in the manufacture of a multilayer printed wiring board, etc., the outer surface of the thermosetting resin composition layer for forming a conductor layer is preferably protected by a protective film, more preferably both outer surfaces of the thermosetting resin composition layer are protected by protective films. The protective film is preferably a metal foil, more preferably a metal foil such as copper foil or aluminum foil.
[0084] The laminate of the present invention preferably further comprises a copper foil on one or both sides thereof.
[0085] The copper foil preferably has a roughness Rz of 2 μm or less. From the viewpoint of adhesion, the copper foil is preferably provided with unevenness. In high frequency applications, if the copper foil has large unevenness, the electrical properties are easily impaired due to the influence of the skin effect, so the copper foil is preferably a low roughness copper foil. The surface roughness (maximum height) Rz of the copper foil is preferably 2.0 μm or less, more preferably 1.0 μm or less. The lower limit of the surface roughness (maximum height) Rz of the copper foil is generally 0.01 μm or more, or 0.1 μm or more.
[0086] The surface roughness (maximum height) Rz of the copper foil on the adhesive layer side is defined as a value obtained by measuring the maximum depth when observing a cross section of the laminate.
[0087] By adjusting the surface roughness (maximum height) Rz of the copper foil surface to 1 μm or less, the use of copper foil can reduce transmission loss in high frequency transmission when the final laminate is used in a circuit board.
[0088] (4) Water absorption rate of the laminate The laminate of the present invention has a water absorption rate of 0.5% by mass or less.
[0089] Water absorption rate The laminate cut to a size of 50 mm x 50 mm was dried at 150°C for 30 minutes, and the mass (w1) in the bone-dry state was measured, and then the specimen was immersed in water. After 24 hours, the specimen was removed from the water, the surface moisture was wiped off, and the mass (w2) was measured.
[0090] The obtained values of w1 and w2 are used to calculate the water absorption rate according to the following formula.
[0091] Formula: Water absorption rate (mass%) = {(w2-w1) / w1}×100 (5) Dielectric constant of laminate (Dk, Df) Relative permittivity (Dk): The dielectric constant indicates how easily an insulating material polarizes when an external electric charge is applied, and has a value that is specific to each material. The more easily a material polarizes, the more likely it is to store electricity, so materials that are less easily polarized (have a small dielectric constant) are advantageous for efficiently transmitting electrical signals. The relative permittivity is the ratio of the dielectric constant of a material when the dielectric constant of a vacuum is set to 1.
[0092] The laminate of the present invention preferably exhibits a lower Dk dielectric constant of 2.8 or less at a frequency of 10 GHz (temperature 23°C, humidity 50% RH). The relative dielectric constant (Dk) of the laminate measured at a frequency of 10 GHz (temperature 23°C, humidity 50% RH) is preferably 5.0 or less, 4.0 or less, more preferably 3.7 or less, 3.5 or less, even more preferably 3.3 or less, 2.8 or less, and particularly preferably 2.7 or less.
[0093] Dielectric tangent (Df): The dielectric tangent indicates the amount of loss when an insulating material releases stored electricity. The smaller the dielectric tangent, the more efficiently the stored electricity is released, and the smaller the transmission loss of the electrical signal.
[0094] The laminate of the present invention preferably exhibits a lower Df dielectric tangent of 0.025 or less at a frequency of 10 GHz (temperature 23°C, humidity 50% RH). The dielectric tangent (Df) of the laminate measured at a frequency of 10 GHz (temperature 23°C, humidity 50% RH) is preferably 0.025 or less, 0.010 or less, 0.009 or less, more preferably 0.008 or less, 0.007 or less, 0.006 or less, even more preferably 0.0055 or less, 0.005 or less, 0.0045 or less, particularly preferably 0.004 or less, 0.0035 or less, 0.003 or less, and 0.0025 or less. The laminate may be characterized by a lower dielectric tangent (Df).
[0095] (6) Layer structure of laminate In the laminate of the present invention, the heat-resistant film preferably has a thickness of 1 μm to 50 μm. The heat-resistant film preferably has a thickness of 2 μm or more and 30 μm or less. By adjusting the thickness of the heat-resistant film to 1 μm to 50 μm, the mechanical strength of the insulating layer and the multilayer printed wiring board becomes sufficient, making it suitable for use in the manufacture of a thin multilayer printed wiring board.
[0096] In the laminate of the present invention, each of the thermosetting resin composition layers preferably has a thickness of 5 μm to 100 μm. By adjusting the thickness of each of the thermosetting resin composition layers to 5 μm to 100 μm, it is possible to achieve a thin multilayer printed wiring board while also achieving surface smoothness, plating formation, circuit embedding properties, insulation properties, etc.
[0097] In the laminate of the present invention, the thickness of each copper foil layer is preferably 1 μm to 38 μm. The thickness of the copper foil is preferably 1 μm to 50 μm, more preferably 2 μm to 40 μm, even more preferably 1 μm to 38 μm, and particularly preferably 3 μm to 30 μm. By adjusting the thickness of the copper foil to 1 μm or more, the laminate has excellent production stability and good handleability. By adjusting the thickness of the copper foil to 50 μm or less, the laminate can easily ensure the flexibility required for an FPC.
[0098] In the laminate of the present invention, the laminate preferably has a total thickness of 12 μm to 326 μm. The total thickness (overall thickness) of the laminate is preferably 10 μm to 500 μm, more preferably 60 μm to 450 μm, and even more preferably 12 μm to 326 μm. By adjusting the total thickness of the laminate to 500 μm or less, it is possible to obtain good flexibility suitable for FCCL, and the handleability during manufacture and use of circuit boards such as FPCs is excellent. By adjusting the total thickness of the laminate to 10 μm or more, it is possible to obtain sufficient strength as an FCCL, and the handleability during manufacture and use of circuit boards such as FPCs is excellent.
[0099] [2] Method for manufacturing a laminate The method for producing a thermosetting low dielectric insulating sheet of the present invention will be described with reference to FIG.
[0100] The laminate can be produced by various methods. For example, a thermosetting resin composition containing an organic solvent is prepared, and the thermosetting resin composition is applied onto a heat-resistant film and dried to form a thermosetting resin composition layer.
[0101] FIG. 2 illustrates a method for producing a three-layer structure having a thermosetting resin composition layer on both sides of a heat-resistant film.
[0102] A polyimide (PI) film, which is an insulating material, is preferably used as the heat-resistant film 101. The thickness of the heat-resistant film 101 is preferably adjusted to be 1 μm to 50 μm.
[0103] A coating material is prepared by dissolving a thermosetting resin in a solvent in advance, and the coating material is applied to the copper foil 103a and the copper foil 103b, respectively, and then dried to obtain the copper foil 104a with the thermosetting resin and the copper foil 104b with the thermosetting resin. The drying conditions are preferably 80°C to 120°C and 3 to 15 minutes.
[0104] After providing a copper foil 104a with thermosetting resin on the upper surface of the heat-resistant film 101 and a copper foil 104b with thermosetting resin on the rear surface of the film 101, the film is pressed in a vacuum press at 200°C for two hours to obtain a three-layer laminate having copper foil 103a and copper foil 103b on the upper and rear surfaces, respectively.
[0105] [3] A multilayer printed wiring board in which an insulating layer is formed by a laminate The laminate of the present invention is for use in an FCCL or an IC substrate.
[0106] The present invention includes an FCCL or IC substrate constructed from a laminate of the present invention.
[0107] The laminate of the present invention is preferably used for a build-up layer of a multilayer printed wiring board.
[0108] The present invention includes a multilayer printed wiring board having an insulating layer formed from the laminate of the present invention.
[0109] The present invention includes a semiconductor device including the multilayer printed wiring board of the present invention. A semiconductor device is manufactured using the multilayer printed wiring board. The semiconductor device is manufactured by mounting a semiconductor chip on the conductive portion of the multilayer printed wiring board.
[0110] The semiconductor chip is preferably an electric circuit element made of a semiconductor material.
[0111] When manufacturing a semiconductor device, the mounting method of the semiconductor chip is preferably one that allows the semiconductor chip to function effectively, and specific examples of such a method include a wire bonding mounting method, a flip chip mounting method, a mounting method using a bumpless build-up layer (BBUL), a mounting method using an anisotropic conductive film (ACF), a mounting method using a non-conductive film (NCF), etc.
[0112] The laminate of the present invention is excellent in dielectric constant and dielectric loss tangent when used for FCCL or IC substrate. EXAMPLES
[0113] The present invention will be specifically described below with reference to examples and reference examples.
[0114] The present invention is not limited to the following specific examples.
[0115] [1] Manufacturing of thermosetting low dielectric insulating sheets Thermosetting low dielectric insulating sheet of Example 1 One embodiment of the thermosetting low dielectric insulating sheet of the present invention will be described with reference to FIG.
[0116] 101 g of polyether resin (JSR Corporation, product name: HC-G0037, non-volatile content: 60% to 65%), 19.5 g of divinylbenzene (NS Styrene Monomer Corporation, product name: DVB960, divinylbenzene purity: 96%, diethylbenzene content: 0.2%), 16.5 g of styrene-butadiene / butylene-styrene block copolymer (Asahi Kasei Chemicals Corporation, product name: Tuftec P2000, styrene content 67%), and 10 g of amino 3.2 g of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBM-603, molecular weight 222.4), 0.4 g of dicumyl peroxide (manufactured by Aldrich, product name: dicumyl peroxide, purity 98%), and 9.4 g of an aluminum salt of organic phosphinic acid (manufactured by Clariant, product name: OP-935) were added and dissolved, and the mixture was mixed and stirred for 15 minutes at 10,000 rpm using a high-speed homogenizer to obtain a paint in which the thermosetting resin was dissolved in the solvent.
[0117] The resulting coating material was dried and the water absorption of the cured product was 0.2% by weight.
[0118] A resin varnish was uniformly applied to the M side of a copper foil (manufactured by Fukuda Metal Foil & Powder Co., Ltd., product name: CF-T4X-SV, thickness: 18 μm) using a bar coater so that the thickness of the thermosetting resin composition layer after drying would be 20 μm, and the foil was dried at 100° C. for 10 minutes to produce a copper foil with a thermosetting resin.
[0119] The obtained copper foil with thermosetting resin was placed on the top and back of a heat-resistant polyimide (PI) film (manufactured by Toray DuPont, product name: Kapton(R) 40LK, thickness: 10 μm) and pressed (hot lamination) in a vacuum press at 200°C for 2 hours to produce the laminate shown in Figure 3.
[0120] The obtained laminate was immersed in an etching solution of sulfuric acid and hydrogen peroxide to remove the copper foil on the top and bottom surfaces.Then, the laminate with only the insulating layer was dried in a box oven at 100°C for 2 hours to prepare a sample for measuring the dielectric constant (Dk, Df).
[0121] The water absorption rate of the laminate of Example 1 was 0.5% by mass or less.
[0122] The obtained sample for measuring the dielectric constant (Dk, Df) was measured for its dielectric constant (Dk, Df) in the 10 GHz band using a network analyzer (manufactured by Anritsu, product name: MS46122B) and a cavity resonator (manufactured by AET, product name: D2303-1), giving the results Dk: 2.68, Df: 0.00249.
[0123] Comparative Example 2: Thermosetting Low Dielectric Insulation Sheet An embodiment of a thermosetting low dielectric insulating sheet as a comparative example will be described with reference to FIG.
[0124] Following Example 1, 101 g of polyether resin, 19.5 g of divinylbenzene, 16.5 g of styrene-butadiene / butylene-styrene block copolymer, 3.2 g of amino-silane coupling agent, 0.4 g of dicumyl peroxide, and 9.4 g of aluminum salt of organic phosphinic acid were added and dissolved, and mixed and stirred with a high-speed homogenizer at 10,000 rpm for 15 minutes to obtain a paint in which the thermosetting resin was dissolved in the solvent.
[0125] The resulting coating material was dried and the water absorption of the cured product was 0.2% by weight.
[0126] In accordance with Example 1, a resin varnish was uniformly applied to the M side of a copper foil (thickness: 18 μm) using a bar coater so that the thickness of the thermosetting resin composition layer after drying would be 6 μm, and the resulting coating was dried at 100° C. for 10 minutes to produce a copper foil with a thermosetting resin.
[0127] Following the procedure of Example 1, a heat-resistant PI film (manufactured by Toray DuPont, product name: Kapton (R) 15 The obtained copper foil with thermosetting resin was placed on the top and back surfaces of a laminate (0LK, thickness: 38 μm) and pressed (hot lamination) in a vacuum press at 200° C. for 2 hours to produce the laminate shown in FIG. 4.
[0128] The copper foils on the top and bottom surfaces were peeled off by immersing the obtained laminate in an etching solution of a mixture of sulfuric acid and hydrogen peroxide, following the procedure of Example 1. The laminate with only the insulating layer was then dried in a box oven at 100°C for 2 hours to prepare a sample for measuring the dielectric constant (Dk, Df).
[0129] The water absorption rate of the laminate of Comparative Example 2 was more than 0.5% by mass.
[0130] Following Example 1, the dielectric constant (Dk, Df) of the obtained sample for dielectric constant (Dk, Df) measurement was measured in the 10 GHz band using a network analyzer and a cavity resonator, and the results were Dk: 2.92 and Df: 0.00369.
[0131] Thermosetting low dielectric insulating sheet of Comparative Example 3 With reference to FIG. 5, one embodiment of a thermosetting low dielectric insulating sheet of a comparative example will be described.
[0132] Following Example 1, 101 g of polyether resin, 19.5 g of divinylbenzene, 16.5 g of styrene-butadiene / butylene-styrene block copolymer, 3.2 g of amino-silane coupling agent, 0.4 g of dicumyl peroxide, and 9.4 g of aluminum salt of organic phosphinic acid were added and dissolved, and mixed and stirred with a high-speed homogenizer at 10,000 rpm for 15 minutes to obtain a paint in which the thermosetting resin was dissolved in the solvent.
[0133] The resulting coating material was dried and the water absorption of the cured product was 0.2% by weight.
[0134] In the same manner as in Example 1, a resin varnish was uniformly applied to the M side of a copper foil (thickness: 18 μm) using a bar coater so that the thickness of the thermosetting resin composition layer after drying would be 6 μm, and the resulting coating was dried at 100° C. for 10 minutes to produce a resin-coated copper foil.
[0135] Following the procedure of Example 1, a heat-resistant PI film (manufactured by Toray DuPont, product name: Kapton (R) 15 The obtained copper foil with thermosetting resin was placed on the top and back surfaces of a laminate (0EN-C, thickness: 38 μm) and pressed (hot lamination) at 200° C. for 2 hours in a vacuum press to produce the structure shown in FIG. 1.
[0136] The copper foils on the top and bottom surfaces were peeled off by immersing the obtained laminate in an etching solution of a mixture of sulfuric acid and hydrogen peroxide, following the procedure of Example 1. The laminate with only the insulating layer was then dried in a box oven at 100°C for 2 hours to prepare a sample for measuring the dielectric constant (Dk, Df).
[0137] The water absorption rate of the laminate of Comparative Example 3 was more than 0.5% by mass.
[0138] Following Example 1, the dielectric constant (Dk, Df) of the obtained sample for dielectric constant (Dk, Df) measurement was measured in the 10 GHz band using a network analyzer and a cavity resonator, and the results were Dk: 3.2 and Df: 0.00642.
[0139] [3] Industrial Applicability The thermosetting low dielectric insulating sheet of the present invention is excellent in dielectric constant and dielectric loss tangent when used for FCCL or IC substrate. Using the thermosetting low dielectric insulating sheet of the present invention, it is possible to provide multilayer printed wiring boards, semiconductor devices, etc. Furthermore, it is possible to provide electrical products such as computers, mobile phones, digital cameras, televisions, etc., and vehicles such as motorcycles, automobiles, trains, ships, and aircraft, which are equipped with these multilayer printed wiring boards, semiconductor devices, etc.
Claims
1. A laminate comprising: The laminate has a three-layer structure including at least a heat-resistant film and a thermosetting resin composition layer on each side of the heat-resistant film, The laminate has a water absorption rate of 0.5% by mass or less, A laminate for use in an FCCL or an IC substrate.
2. The laminate has a Dk dielectric constant of 2.8 or less at 10 GHz; and The Df dielectric tangent of the laminate at 10 GHz is 0.025 or less. The laminate according to claim 1.
3. The heat-resistant film is a polyimide film, The thermosetting resin composition layer is a resin composition layer made of a polyether-based resin. The laminate according to claim 1.
4. 2. The laminate according to claim 1, wherein the thermosetting resin composition layer contains silica.
5. 2. The laminate according to claim 1, wherein the thermosetting resin composition layer comprises at least one flame retardant selected from the group consisting of a phosphinate compound, a phosphine oxide compound, a polyphosphate compound, and a phosphonium salt compound.
6. The laminate according to claim 1 , further comprising a copper foil on one or both sides of the laminate.
7. The laminate according to claim 6, wherein the copper foil has a roughness Rz of 2 μm or less.
8. The heat-resistant film has a thickness of 1 μm to 50 μm, The thermosetting resin composition layer has a thickness of 5 μm to 100 μm. The copper foil has a thickness of 1 μm to 38 μm for each layer, The laminate has a total thickness of 12 μm to 326 μm. The laminate according to claim 6.
9. 9. An FCCL or IC substrate comprising the laminate according to claim 1.
Citation Information
Patent Citations
Insulating resin sheet
JP2014187091A
Cited By
Metal-clad laminate and metal with resin
WO2026204142A1